Skinfold Thickness: An Anthropometric Parameter to Determine the Nutritional Status among College Girls (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Body fat plays a crucial role in human physiology, and its distribution throughout the body influences the health outcomes (1). The types of fats differ based on location, function, and metabolic impact. Anatomically, there are several different depots of fat, including subcutaneous, visceral, intramuscular, intermuscular, and ectopic (2). Skinfold thickness measurement at common sites of the body, like triceps, biceps, subscapular, suprailiac, and thigh regions, provides an estimate of the body fat for health professionals to assess the health of a person (3). This research examines the skinfold thickness measurements of 106 female students between the ages of 16 and 25 years to evaluate their nutritional status. The measurement results of skinfold vary across participant girls, ranging from 47 mm to 140 mm, indicating substantial differences in subcutaneous fat. The Sum of skinfold (SSF) of samples Around 37.5% of the sample fell into the high-adiposity category (SSF >100 mm), while 33% had moderate levels of adiposity (SSF 70–100 mm). Subscapular and suprailiac skinfold measurements were used to measure central adiposity, which was highest in girls with higher body weights.